DINAMIKA PIDANA MATI DALAM KUHP BARU: PEMBARUAN HUKUM PIDANA DAN TANTANGAN IMPLEMENTASI - Agrarini, Lintang Sely Puspita (Jurnal Ilmiah Advokasi, 2025)
The dynamics of capital punishment in Indonesia have undergone significant transformation in line with the revision of the Criminal Code (KUHP). This study aims to analyze changes in capital punishment policy in the new KUHP and identify challenges to its implementation. The method used is a normative legal approach with a statute approach. The results show that capital punishment in the new KUHP is positioned as an alternative punishment imposed conditionally, with a probation period of 10 years. This approach reflects an orientation toward rehabilitation and respect for human rights. However, its implementation faces challenges from legal, ethical, and socio-political aspects, particularly regarding legal uncertainty and international criticism. More progressive legal reforms are expected to promote harmonization between national criminal law and international human rights principles. Keywords: Death Penalty; New Criminal Code ; Criminal Law Reform; Human Rights